Determining the Demographic and Psychosocial Factors That Influence Smoking Addiction - Morsünbül, Ümit (Addicta: The Turkish Journal on Addictions, 2019)
The aim of this study is to determine the demographic and psychosocial factors influencing smoking addiction. The research group consists of 429 (257 female, 172 male) university students and between the ages of 18- 27 years old (M= 20.66 ± 1.60). The Fagerström Test for Nicotine Dependence, Utrecht-Management of Identity Commitments Scale, Quick Big Five Personality Test, Autonomous-Related Self in Family Scales, and Inventory of Parent and Peer Attachment were used for collecting data. The results of this study indicate demographic and psychosocial factors to be related to smoking and have revealed the necessity of considering demographic and psychosocial factors while preparing programs to prevent smoking. To